2013
DOI: 10.1167/iovs.12-10317
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Profiling of Major Neutral Lipid Classes in Human Meibum by Direct Infusion Electrospray Ionization Mass Spectrometry

Abstract: PURPOSE. The purpose of this investigation was to better understand lipid composition in human meibum.METHODS. Intact lipids in meibum samples were detected by direct infusion electrospray ionization mass spectrometry (ESI-MS) analysis in positive detection mode using sodium iodide (NaI) as an additive. The peak intensities of all major types of lipid species, that is, wax esters (WEs), cholesteryl esters (CEs), and diesters (DEs) were corrected for peak overlapping and isotopic distribution; an additional ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
135
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(147 citation statements)
references
References 82 publications
9
135
3
Order By: Relevance
“…Similar to WE FA chains, the CE species detected at the highest abundance contained esterified FA chains of 24:0, 25:0, and 26:0. This is in agreement with the recent study by Chen, 16 as well as earlier studies of Chen, 14 Lam, 13 and Nicolaides. 17 Butovich et al 18 characterized CE speciation in meibum by HPLC atmospheric pressure chemical ionization MS, and their study reported CE 24:0, CE 25:0, and CE 26:0 as highly abundant, but also reported CE 26:1 and 28:1 as highly abundant.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similar to WE FA chains, the CE species detected at the highest abundance contained esterified FA chains of 24:0, 25:0, and 26:0. This is in agreement with the recent study by Chen, 16 as well as earlier studies of Chen, 14 Lam, 13 and Nicolaides. 17 Butovich et al 18 characterized CE speciation in meibum by HPLC atmospheric pressure chemical ionization MS, and their study reported CE 24:0, CE 25:0, and CE 26:0 as highly abundant, but also reported CE 26:1 and 28:1 as highly abundant.…”
Section: Discussionsupporting
confidence: 94%
“…15 This is also in agreement with the recent ESI-MS study by Chen et al, 16 who report the highest abundance WE species of WE 42:1, WE 43:1, and WE 44:1. Similar to WE FA chains, the CE species detected at the highest abundance contained esterified FA chains of 24:0, 25:0, and 26:0.…”
Section: Discussionsupporting
confidence: 91%
“…[6, 29] However, for each peak of a certain m / z there could be multiple isomers. Dissociation of each peak generated mixed fragments from different isomers.…”
Section: Resultsmentioning
confidence: 99%
“…The double bond effect and neutral molecule adduct formation observed for dissociation of wax esters could be helpful for identification and quantification of wax esters in biological samples. Current work is ongoing to utilize these fragmentation patterns in conjunction with our earlier work of profiling wax esters in meibum [29] to identify and quantify each isobaric species composition in meibum samples from the corresponding MS/MS spectra. [6]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation